A group of grapevine MYBA transcription factors located in chromosome 14 control anthocyanin synthesis in vegetative organs with different specificities compared with the berry color locus. (17th May 2017) - Matus, José Tomás; Cavallini, Erika; Loyola, Rodrigo; Höll, Janine; Finezzo, Laura; Dal Santo, Silvia; Vialet, Sandrine; Commisso, Mauro; Roman, Federica; Schubert, Andrea; Alcalde, José Antonio; Bogs, Jochen; et al.
Summary: Grapevine organs accumulate anthocyanins in a cultivar‐specific and environmentally induced manner. The MYBA1 ‐ A2 genes within the berry color locus in chromosome 2 represent the major genetic determinants of fruit color. The simultaneous occurrence of transposon insertions and point mutations in these genes is responsible for most white‐skinned phenotypes; however, the red pigmentation found in vegetative organs suggests the presence of additional regulators. This work describes a genomic region of chromosome 14 containing three closely related R2R3‐MYB genes, named MYBA5, MYBA6 and MYBA7 . Ectopic expression of the latter two genes in grapevine hairy roots promoted anthocyanin accumulation without affecting other phenylpropanoids. Transcriptomic profiling of hairy roots expressing MYBA1, MYBA6 and MYBA7 showed that these regulators share the activation of late biosynthetic and modification/transport‐related genes, but differ in the activation of the FLAVONOID‐3′5′‐HYDROXYLASE ( F3′5′H ) family. An alternatively spliced MYBA6 variant was incapable of activating anthocyanin synthesis, however, because of the lack of an MYC1 interaction domain. MYBA1, MYBA6.1 and MYBA7 activated the promoters of UDP‐GLUCOSE:FLAVONOID 3‐O‐GLUCOSYLTRANSFERASE ( UFGT ) and ANTHOCYANIN 3‐O‐GLUCOSIDE‐6″‐O‐ACYLTRANSFERASE ( 3AT ), but only MYBA1 induced F3′5′H in concordance with the low proportion of tri‐hydroxylated anthocyanins found in MYBA6‐A7 hairy roots. This putative new color locus is related to the red/cyanidic pigmentation of vegetative organs in black‐ and white‐skinned cultivars, and forms part of the UV‐B radiation response pathway orchestrated by ELONGATED HYPOCOTYL 5 (HY5). These results demonstrate the involvement of additional anthocyanin regulators in grapevine and suggest an evolutionary divergence between the two grape color loci for controlling additional targets of the flavonoid pathway. Significance statement: While the R2R3‐MYBA genes within the grapevine berry color locus represent the major genetic determinants of fruit color variation, a novel locus located on a different chromosome is responsible for the coloring of vegetative organs. The MYBA genes from this new region have diverged in expression, function and regulation (reflecting both subspecialization and subfunctionalization processes) and differ from the previously characterized berry MYBAs in their capacity to regulate the tri‐hydroxylated sub‐branch of the anthocyanin pathway.